2019
DOI: 10.1002/lt.25651
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Pressure at Liver Transplant Evaluation Predicts Renal Histology in Candidates With Renal Dysfunction

Abstract: Renal dysfunction is common in liver transplantation (LT) candidates, but differentiating between reversible and irreversible renal injury can be difficult. Kidney biopsy might be helpful in differentiating reversible from irreversible renal injury, but it is associated with significant complications. We aimed to identify pre‐LT predictors of potentially reversible renal injury using histological information obtained on pre‐LT renal biopsy. Data on 128 LT candidates who underwent pre‐LT kidney biopsy were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The relatively high preoperative serum creatinine may result from the unavoidable whole body ischemia occurring during OLT (8,19). To prioritize the blood supply to other important organs, a transitory insufficient supply to the kidney may occur, causing tubular necrosis (20). This study is limited by its single-center, retrospective design and only moderate number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high preoperative serum creatinine may result from the unavoidable whole body ischemia occurring during OLT (8,19). To prioritize the blood supply to other important organs, a transitory insufficient supply to the kidney may occur, causing tubular necrosis (20). This study is limited by its single-center, retrospective design and only moderate number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Post-LT immunosuppression management has previously been described and did not vary during the 20-year study period. (16,17) Briefly, the renal dysfunction group (Cr >1.5 or on RRT) received induction treatment with an interleukin-2 receptor blocker with delayed calcineurin inhibitor (CNI) introduction, whereas the patients without renal dysfunction received no induction treatment. Intravenous methylprednisolone starting from the day of the surgery was given for 4 to 5 doses followed by oral prednisone, which was tapered to 5 mg/day and later discontinued by the fourth post-LT month.…”
Section: Post-lt Managementmentioning
confidence: 99%
“…[2,3] However, the decision to proceed with SLK is not always clear. [4] Indeed, in some patients with severe acute kidney injury (AKI) related to hepatorenal syndrome, improvement in kidney function can occur following LT. [5] Brennan et al [6] demonstrated that up to 87% of patients with renal dysfunction who received LT had improvement in renal function within 1 month of transplant and that the prevalence of stage 4 or 5 chronic kidney disease after 1 year was as low as 6.8%. Similarly, a meta-analysis of 38 studies found that only 7% of patients undergoing LT had AKI necessitating dialysis postoperatively.…”
Section: Introductionmentioning
confidence: 99%